Numarul 1, (3) + 1,(4) + 1,(5)+1,(6)=
Răspunsuri la întrebare
Răspuns de
2
Răspuns
6
Explicație pas cu pas:
1 , ( 3 ) + 1 , ( 4 ) + 1 , ( 5 ) + 1 , ( 6 ) =
= ( 13 - 1 ) / 9 + ( 14 - 1 ) / 9 + ( 15 - 1 ) / 9 + ( 16 - 1 ) / 9
= ( 12 / 9 ) + ( 13 / 9 ) + ( 14 / 9 ) + ( 15 / 9 )
= ( 25 / 9 ) + ( 14 / 9 ) + ( 15 / 9 )
= ( 39 / 9 ) + ( 15 / 9 )
= 54 / 9 = 6
Alte întrebări interesante
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
8 ani în urmă
Matematică,
9 ani în urmă
Chimie,
9 ani în urmă
Ed. tehnologică,
9 ani în urmă
Fizică,
9 ani în urmă
Matematică,
9 ani în urmă